Working towards the isolation of stable organometallic alkane complexes - Veasy, Agata (2024)
Chapter 1 An introduction to the photochemistry of organometallic alkane and noble gas complexes, which have been the subject of this Thesis is outlined here. Time-resolved spectrometry and computational methods are also briefly described.